POTENSI DAN STRATEGI PENGEMBANGAN EKOWISATA MADU DI DESA TELAGA LANGSAT KECAMATAN TAKISUNG KABUPATEN TANAH LAUT - Dewi Lestari; Rina Muhayah Noor Pitri; Muhammad Helmi (Jurnal Sylva Scienteae, 2020)
Identifying the potential and strategies for Honey Ecotourism development. The method used is field observations and interviews using purposive sampling descriptive analysis and SWOT analysis. Honey Ecotourism research location in Telaga Langsat Village. The results showed that Honey Ecotourism has a very diverse tourism potential such as honey products, bee pollen, propolis and community forest plant seeds. Potential flora, fauna and various kinds of tourism activities such as honey picking tours, student tours, and training in honey bee cultivation and can be used as research sites. The results of SWOT analysis is in quadrant I which means it is in a very favorable position or situation. Internal strengths can minimize weaknesses, and threats will be resolved, if existing managers make the most of the opportunities available to encourage development with aggressive strategies through three approaches. The first is the cost of providing the best quality at a low price. Both tourism activities that can be carried out are unique and different from other tourist attractions. The third focuses on visitors from children, adolescents, to adults. So that the Honey Ecotourism can develop and be beneficial for managers, governments, communities and visitors.Keywords: Potency; Development Strategy; Ecotourism Honey; SWOT Analysis